2015
DOI: 10.1088/0004-637x/800/2/119
|View full text |Cite
|
Sign up to set email alerts
|

G359.97-0.038: A Hard X-Ray Filament Associated With a Supernova Shell-Molecular Cloud Interaction

Abstract: We present the first high-energy X-ray (>10 keV) observations of the non-thermal filament G359.97-0.038 using the Nuclear Spectroscopic Telescope Array (NuSTAR). This filament is one of approximately 20 X-ray filaments of unknown origin located in the central 20 pc region in the Galactic Center near Sgr A*. Its NuSTAR and Chandra broadband spectrum is characterized by a single power law with Γ = 1.3 ± 0.3 that extends from 2 to 50 keV, with an unabsorbed luminosity of 1.3 × 10 33 erg s −1 (d/8 kpc) 2 in the 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…The solid ellipse (white) illustrates the FWHM of the fit to the unresolved emission. Emission consistent with the pulsar wind nebula G359.95-0.04 13 , as well as fainter emission from the Cannonball 19 and non-thermal filament G359.97-0.038 14 , is also visible. The dashed ellipse (green) indicates the soft X-ray extent of Sgr A East…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…The solid ellipse (white) illustrates the FWHM of the fit to the unresolved emission. Emission consistent with the pulsar wind nebula G359.95-0.04 13 , as well as fainter emission from the Cannonball 19 and non-thermal filament G359.97-0.038 14 , is also visible. The dashed ellipse (green) indicates the soft X-ray extent of Sgr A East…”
mentioning
confidence: 84%
“…The image is dominated by this feature, whose spectrum and localization within several parsecs of Sgr A* distinguish it from other unresolved X-ray emission in the Galaxy, and which has no obvious correlation with radio images of the dense molecular gas of the circumnuclear disk 11 or the dust and gas of Sgr A West 12 . The features prominent in soft-X-ray images no longer visibly contribute, with the exception of bright pointlike emission from the pulsar wind nebula G359.9520.04 13 and fainter emission from the X-ray filament G359.9720.038 14 and the Cannonball 15 neutron star. .…”
mentioning
confidence: 98%
“…NuSTAR studies of a few bright diffuse sources in the GC region are also found in the literature: Zhang et al (2014) and Nynka et al (2015) report detailed NuSTAR hard X-ray studies of the X-ray filaments SgrA-E knot and G359.97-0.038, respectively; Krivonos et al (2014) and Zhang et al (2015) present the detailed NuSTAR analysis results of the diffuse hard X-ray emission from the Arches cluster and the SgrB2 cloud, respectively. Complementing the survey of the GC region, a similar NuSTAR survey was conducted on the Norma sprial arm region in parallel.…”
Section: Introductionmentioning
confidence: 90%
“…The prominent diffuse structures seen in the trial maps include the SgrA complex, a few molecular clouds and X-ray filaments including G359.89-0.08 (Sgr A-E; Zhang et al 2014), the Arches Cluster ), G359.97-0.038 (Nynka et al 2015), and the SgrB2 cloud . These regions are excluded in our point source analysis.…”
Section: A2 Diffuse Emissionmentioning
confidence: 99%
“…Hard X-ray Sources The SNR ejecta / shocked clump interpretation of hard X-ray sources within SNR-MC interaction region can potentially explain a large population of hard X-ray sources in dense environments of star-forming regions, such as the Galactic center. In the NuSTAR Galactic center survey, we detected a few hard X-ray sources in the SNR-MC interaction sites (Zhang et al 2014;Nynka et al 2015). Among them, G359.97-0.038 is most likely arising from SNR-MC interaction.…”
Section: Enlightenment On Nature Of Galactic Centermentioning
confidence: 99%